RANCANG BANGUN SISTEM PENGEMUDIAN ELEKTRIK PADA MOBIL LISTRIK AGNIJAYA WEIMANA - Mustika Wiyasa, I Kd; Satya Kumara, Nyoman; Raka Agung, I Gusti Agung Putu (Jurnal SPEKTRUM, 2023)
Electric energy can be used as a substitute for oil fuel. One of the efforts to address air pollution is through the Energy-Efficient Car Contest (KMHE), which emphasizes vehicle efficiency. In this study, the electric propulsion system in the electric car WEIMANA, which focuses on the selection of an electric motor, conducted tests on a BLDC motor to determine the required power of the BLDC motor. In the selection of the electric motor, calculations were made for rolling resistance, aerodynamic resistance of the car, power, and required torque. Based on the discussion's results, the chosen motor is the qs-motor brand with a capacity of 800 W, 500 RPM, torque of 80 Nm, and operating voltage of 48 – 70 VDC. The magnitudes of rolling resistance, aerodynamic resistance of the car, power, and torque are 16.67 N, 7.83 N, 864.7 W, and 59.22 Nm, respectively. The selected motor has been able to propel the WEIMANA car with driver weights of 45 kg, 55 kg, and 65 kg at speeds of 20 km/h and 30 km/h. The highest average power efficiency of the controller is 90.31% with a driver weight of 55 kg. The highest average power efficiency of 88.03% is achieved at a speed of 20 km/h.